2020
DOI: 10.1007/s10640-020-00453-w
|View full text |Cite
|
Sign up to set email alerts
|

Five Lessons from COVID-19 for Advancing Climate Change Mitigation

Abstract: The nexus of COVID-19 and climate change has so far brought attention to short-term greenhouse gas (GHG) emissions reductions, public health responses, and clean recovery stimulus packages. We take a more holistic approach, making five broad comparisons between the crises with five associated lessons for climate change mitigation policy. First, delay is costly. Second, policy design must overcome biases to human judgment. Third, inequality can be exacerbated without timely action. Fourth, global problems requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 123 publications
2
65
0
6
Order By: Relevance
“…Our findings recall existing literature regarding the way people perceive and respond to different threats. As a first consideration, whether a threat is perceived as "imminent" changes reactions to it dramatically: the COVID-19 pandemic has clearly demonstrated that societies pay a high price when facing an imminent threat, both financially and in terms of restrictions, such as lockdowns [61]. In addition to this, when faced with a threat, people tend to rely on their own past experiences with similar events to determine the ease with which they will cope.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings recall existing literature regarding the way people perceive and respond to different threats. As a first consideration, whether a threat is perceived as "imminent" changes reactions to it dramatically: the COVID-19 pandemic has clearly demonstrated that societies pay a high price when facing an imminent threat, both financially and in terms of restrictions, such as lockdowns [61]. In addition to this, when faced with a threat, people tend to rely on their own past experiences with similar events to determine the ease with which they will cope.…”
Section: Discussionmentioning
confidence: 99%
“…However, these reductions will not be enough to meet the Paris agreement. This suggests a need for a much deeper social change coupled with a green transformation that decouples economic activity and carbon emissions [34]. We still lack a clear understanding of how such an economy could look like but we posit one possibility in the Section 5.3.…”
Section: Emissions Reductions At the Most Expensive Costmentioning
confidence: 99%
“…The argument in favor of increasing carbon prices have in the past been depicted as an intolerable burden to society. After COVID-19, it will be difficult to discard economic arguments against climate policy in this way, as the economic costs of limiting climate change to below two degrees are projected to be orders or magnitude lower than those of COVID-19 [34].…”
Section: Emissions Reductions At the Most Expensive Costmentioning
confidence: 99%
“…Directly, global warming might have provided more suitable conditions for infectious diseases to outbreak 11 and indirectly, migrations driven by climate stressors 12 leave numerous homeless people who live in refugee camps without proper social distancing strategies or healthcare extremely vulnerable to epidemics 13 . Actually, climate change and the pandemic are markedly similar in terms of devastating global impacts and demand for immediate government intervention 5,14,15 . Therefore, tackling climate change problem amid the pandemic and facilitating green socioeconomic recovery programs that address climate mitigation and other environmental goals has received increasing attention from policy makers and scholars 5,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The current study intended to make contributions mainly in two ways. First, public perception of the severity of threats is indispensable in the mitigation of both the pandemic and climate change 14,20 , and there exists many above-mentioned parallel characteristics between these two crises 14,15,20 ; nonetheless, to the best of our knowledge, there have been little direct exploration of the relationship between public pandemic risk perception and climate change concern; more speci cally, whether and how pandemic risk perception would impact on climate change concern during COVID-19 outbreak should receive more attention given the overall increased awareness of green recovery. Accordingly, the current study aims to offer some preliminary insights into the potential predictive effect of pandemic risk perception on climate change concern to better inspire climate mitigation and adaption over the pandemic time.…”
Section: Introductionmentioning
confidence: 99%